O Gato como consciência em Coraline, de Neil Gaiman - Simões, Ana Carolina Andrade (2019)
Studies of the imagination in texts of children‘s literature have been quite accomplished over the years. According to the historical moment, children's literature attains, as one of its functions, to instruct or simply to contribute to the creative-imaginative capacity of children. In the novel Coraline, by Neil Gaiman, the title of children‘s literature does not restrict the reading public to children and adolescents, on the contrary, it instigates people of all ages to meet the young Coraline and her worlds. This work presents an analysis of the narrative of Coraline from theories that deals with the fantastic, the gothic and the uncanny elements, such as those seen in Freud (1980), Todorov (2006), Sá (2003), Osório (2010), and Camarani (2014), in order to reinforce the general objective of unveiling, with the help of Freud's psychoanalytic theory, whether the black cat character is actually the materialization of the young Coraline‘s consciousness - a factor that has been of great importance for the development of the protagonist in the plot. From this research, it is hoped to open another perspective in the field of discussion about animal characters as protagonists‘ helpers, regarding decision-making, opinion influencers and faithful friends. In addition, it is also expected that, from this work, people will see how important the stories for children and youth are in the formation of human beings, especially in regards of the way in which their authors construct their literary worlds.